NEPRAVILNA ISHRANA KAO KARDIOMETABOLIČKI FAKTOR RIZIKA - Vučević, Danijela (Medical Research, 2022)
A well-balanced diet is an important factor in the promotion and maintenance of good health throughout one’s life. The role of a diet as a determinant of chronic non-communicable diseases is well established and it occupies a prominent position in prevention. The burden of chronic diseases is rapidly increasing worldwide. Namely, chronic non-communicable diseases are the leading cause of death worldwide. Preterm mortality in people under 70 accounts for over 40% of the total of 38 million deaths due to chronic non-communicable diseases. Obesity, metabolic syndrome, and diabetes mellitus are also showing worrying trends, not only because they already affect a large part of the population, but also because they have started to occur earlier in life. Thus, the metabolic syndrome is a cluster of more or less related metabolic and cardiovascular derangements including visceral obesity, insulin resistance, dyslipidemia, hypertension and glucose intolerance. This syndrome is characterized by a primary cellular defect in insulin action due to disorders in insulin signal transduction (insulin is unable to adequately achieve its biological effects). Under these conditions, insulin resistance, in combination with hyperinsulinemia causes numerous metabolic and cardiovascular disorders, which are leading causes of morbidity and mortality worldwide. From the pathophysiological point of view, a diet rich in carbohydrates and saturated fats significantly contributes to the development of many chronic diseases (diabetes mellitus type 2, hypertension, accelerated atherosclerosis and its cardiovascular and cerebrovascular complications, nonalcoholic fatty liver disease, polycystic ovary syndrome, and some malignant diseases – breast cancer, etc.). In this review, we provide an overview of recent literature data and practical knowledge related to an unbalanced diet as a cardiometabolic risk factor. Further investigations in the field of molecular prevention may contribute to the development of new biomarkers, or help the setting of strategies for molecular prevention of chronic non-communicable diseases. In other words, they represent the directive for applying nutrigenomics to population sciences.